A SThM probe optimization and its time-space multi-scale modeling. (December 2016) - Lenczner, Michel; Yang, Bin; Bontempi, Alexia; Teyssieux, Damien; Cogan, Scott; Janus, Pawel; Köhler, Bernd; Ratier, Nicolas
Abstract: We present two aspects of modeling and design of a Scanning Thermal Microscopy (SThM) probe built by microfabrication techniques. An optimized design based on a full parametrization of its geometry is calculated using a multi-criteria optimization technique after a drastic selection of the most sensitive geometrical parameters. The optimization is carried out in the static regime. We also report a new time-space multi-scale model of the probe operating in active mode and heated with a combination of DC and modulated harmonic current sources, a case where the simulation takes too long to be used in a regular design process. The model derivation is based on an asymptotic methods related to high frequency periodic source. Precisely, the model distinguishes between two time scales and two space scales related to the low and high frequency phenomena. Simulation results show the potential of the model in terms of accuracy and computation speed and are compared to experimental results.